Designing and developing single phase distance protection model / Mohammed Zulkarnain Abdullah - Abdullah, Mohammed Zulkarnain (2006)
Power system protection is the most important part beside load flow studies. The objective of the system protection system design is to minimize the fault that can damage the system. This paper presents a case study how distance protection relay operate and function when fault occurs at certain zone in line impedance. Since, there is impossible to study within the real part of the transmission line that can cause a hazard. The idea came to designing and developing single phase distance protection model in power system where the application nearly the same as the real one. This project can be a basic reference to the students who want to study about the system protection. This project divided into two section, hardware and PIC controller. About PIC controller, it has been making by my partner. The case study is involve hardware design to develop the distance protection model for the single phase of the power system and switching relay is control by Peripheral Interface Controller (PIC). It is related with the software design to make the hardware function properly.